Gender identity and sexual orientation: sexuality in the school context (Research, Society and Development, 2019)
The present text has the objective of discussing the diversity of genders and sexual orientations, which compose the school context under the teaching perspective. Faced with such phenomena, a survey was carried out with 12 high school teachers from a public school in the city of Cuiabá-MT. In qualitative research, the senses attributed by these teachers to the phenomenon of sexuality and its manifestations in the context of their praxis were investigated. For analyzing the fragments of reports seized through a semi-structured interview, we adopted, as a theoretical-methodological view, Social Constructionism through the analysis of linguistic repertoires and investigated the production of meanings enunciated by discursive practices. Sexuality, although treated as a phenomenon 'natural' to every human being, presents itself in its complexity and diversity as a social construct, as well as the various forms of identities. Thus, discourses on the lack of information about such phenomena appear, which makes it impossible for the educators to actually carry out the transversality proposed by the National Curricular Parameters (NCPs). The school is still fragile and lacking in training to deal with issues involved in sexuality, whether in dialogue about gender, orientation or even sexual diversity. This observed reality needs to be transformed through curricula, norms, and methodologies that consider the diversity of gender, cultures, ethnicities, classes, and other human subjectivities present in the educational environment. In this movement, the transversality of themes such as sexuality will become possible, as well as the effective construction of new knowledge and knowledge.